Conflict as a point of no return: Immigrant and internally displaced journalists in Ukraine. (October 2020) - Voronova, Liudmila
The Ukrainian Euromaidan protests in 2013, alongside the Brexit vote and the so-called 'refugee crisis', have strongly changed the imaginary of Europe. Apart from ideological shifts and geopolitical changes, the situation in Ukraine has led to a geographic relocation and displacement of media producers and audiences alike. Yet, in the Ukrainian context and beyond, little is known about dislocated journalists in conflict situations. This article addresses the specific experiences of immigrant and internally displaced journalists, their imagined audiences and the overarching construction of post-revolutionary Ukraine as an imagined community. The argument draws empirically from the dislocatory experiences and relocatory trajectories of two groups: immigrant journalists, who moved to Ukraine from Russia, and journalists who migrated internally – to Kyiv and other government-controlled Ukrainian regions from Crimea and non-government-controlled areas of Donbas. For immigrant and internally displaced journalists, the search for new identities and positions is strongly related to their imagination of the audiences. The journalists notice a simultaneous fragmentation and unification of the audiences driven by both top-down and down-up intentions of post-revolutionary nation building. They hope to contribute to turning the fragmented communities into a media nation that will perceive them as 'us'.